2009
DOI: 10.1002/ana.21732
|View full text |Cite
|
Sign up to set email alerts
|

Limb‐girdle muscular dystrophy type 2D gene therapy restores α‐sarcoglycan and associated proteins

Abstract: Objectives Alpha-sarcoglycan deficiency is a severe form of muscular dystrophy (LGMD2D) without treatment. Gene replacement represents a strategy for correcting the underlying defect. Questions related to this approach were addressed in this clinical trial, particularly the need for immunotherapy, and persistence of gene expression. Methods A double-blind, randomized controlled trial using rAAV1.tMCK.hSGCA injected into the extensor digitorum brevis (EDB) muscle was conducted. Control sides received saline. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
153
3
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 194 publications
(161 citation statements)
references
References 24 publications
(31 reference statements)
4
153
3
1
Order By: Relevance
“…This may have important clinical consequences, based on the current understanding of the fate of the capsid after vector transduction of the target cells. If, as has been proposed, transduced cells are characterized by presentation of capsid antigens via MHC class I, then the cells would be vulnerable to destruction by cognate CD8 ϩ T cells for as long as capsid is presented on the cell surface; a recent study 32 showing upregulation of MHC class I expression on muscle fibers after AAV-1 gene transfer supports this hypothesis. However, immune responses that develop slowly and do not become detectable until later time points 33 may in fact encounter few or no targets for immune-mediated destruction.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This may have important clinical consequences, based on the current understanding of the fate of the capsid after vector transduction of the target cells. If, as has been proposed, transduced cells are characterized by presentation of capsid antigens via MHC class I, then the cells would be vulnerable to destruction by cognate CD8 ϩ T cells for as long as capsid is presented on the cell surface; a recent study 32 showing upregulation of MHC class I expression on muscle fibers after AAV-1 gene transfer supports this hypothesis. However, immune responses that develop slowly and do not become detectable until later time points 33 may in fact encounter few or no targets for immune-mediated destruction.…”
Section: Discussionmentioning
confidence: 92%
“…The relationship of T-cell responses, changes in muscle enzymes, and long-term expression of the donated gene requires further study. Recent studies in mice and humans 32,41 showed apoptosis of lymphocytes infiltrating skeletal muscle after AAV-mediated gene transfer, a phenomenon that may play a role in shaping clinical responses to T-cell activation, and may also account for variability of responses among subjects receiving equivalent vector doses.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, although not a current concern in the proposed ongoing clinical trial for Pompe disease, the potential for vertical transmission of the vector, shown through real-time PCR of fractionated semen samples from rabbits, demonstrated a very low likelihood of this occurring. Another clinical study for limb girdle muscular dystrophy using an AAV1-alphasarcoglycan (AAV1-aSG) was initiated as a result of additional toxicity studies (unpublished) in C57Bl/6 and aSG knockout mice (Mendell et al, 2009). These animals were euthanized on 30, 60, 90, 180, and up to 540 days postinjection in the quadriceps.…”
Section: Discussionmentioning
confidence: 99%
“…on May 12, 2018. by guest www.bloodjournal.org From clinical outcome was more difficult to establish. Furthermore, several factors appear to influence the outcome of gene transfer in muscle, including upregulation of MHC I expression in some settings, 100,101 apoptosis of reactive T cells, 101,103 immunomodulatory properties of the transgene product 17,98,104 as well as transgene immunogenicity (vide infra), and baseline levels of inflammation within the target tissue. 105 Additional studies are needed to identify determinants that may lead to a destructive immune response following AAV vector administration to muscle and to establish whether IS is needed (eg, when large doses of AAV vectors are administered).…”
Section: Capsid T-cell Responses In Muscle Gene Transfermentioning
confidence: 99%